Study on the Social Effects of New Media of "People’s Daily" in COVID-19 Epidemic - Qian, Gong (Historia y Comunicación Social, 2021)
This paper aims to study the social effects of new media of People’s Daily, one of the world’s top 10 newspapers, on its coverage of COVID-19 epidemic. Due to its unique advantages in news reporting, new media plays an irreplaceable role in the reporting of public health emergencies. In the face of COVID-19 epidemic, the three major new media platforms of People’s Daily (Microblog, WeChat and Tik Tok) have differentiated their reports according to their platform characteristics and audience preferences, thus effectively fulfilling their media functions. By collecting and analyzing relevant data of COVID-19 coverage by the three media platforms of People’s Daily, this paper explores the change trend of the number of reports and their content, and points out the organic integration of media platforms can optimize the communication effect in Chinese society.